OP0267-HPR "I NEVER THOUGHT EXERCISE COULD HELP IMPROVE MY SLEEP": EXPERIENCES OF PEOPLE WITH RHEUMATOID ARTHRITIS ON THE IMPACT OF EXERCISE ON SLEEP. (2nd June 2020) - Mckenna, S.; Larkin, L.; Donnelly, A.; Fraser, A.; Esbensen, B. A.; Kennedy, N.
Abstract : Background: OMERACT has identified sleep quality as one of the key outcomes for people with RA [1]. Poor sleep and reduced total sleep time (TST) are common complaints among people with RA. Poor sleep can in turn lead to deterioration in function, reduce activity levels and also impact mental health. Although sleep and mental health outcomes have been identified as important, they are frequently not measured in clinical trials. Involving key stakeholders, like people with RA, is important when designing exercise interventions as it allows consideration of particular issues that may influence future intervention delivery. This study involved people with RA who participated in a pilot RCT group exercise class to improve sleep quality. Objectives: To explore participants experiences of an exercise intervention in improving sleep quality and TST, to capture their reality. Methods: A descriptive qualitative study design of face-to-face semi-structured interviews was employed. The interview schedule explored a number of areas: experience of the intervention; outcome measures used; views regarding the intervention; perceptions regarding exercise and sleep and the impact on sleep. Interviews were transcribed verbatim by a professional transcriber. Inductive thematic analysis was used as an analytical approach. Interview transcripts were read, notes made, and ideas formulated to facilitate coding. The research team searched for patterns, analysed and coded the data, and generated themes and sub-themes. Themes were reviewed by the research team to check if they worked in relation to the coded extracts and the entire data set. The COREQ checklist provided guidance. Results: Twelve females participated with a mean age of 58 (SD 7.4); mean RA diagnosis of 9.9 (SD 7.4) years; moderate to severe disability (HAQ-DI: 1.5 (SD 0.60). Four main themes were generated: 1) Positive impact of exercise on sleep - "I really didn't think any type of exercise would help me sleep better if I'm honest."; 2) Positive experiences of exercise intervention to improve sleep -"I learnt so much regarding walking that I didn't even think about."; 3) Clear mental health benefits – "If you don't sleep well then it will have a knock-on effect to your mental health" ; 4) Achieving empowerment and ownership when exercising - "I feel empowered now and confident that I'm not doing harm to myself". The findings demonstrated that participants were clearly surprised that exercise could improve sleep. Conclusion: In a variety of inflammatory conditions exercise is recommended as an effective intervention for the treatment of sleeping disorders. Although there is a growing consensus that exercise will benefit sleep, research is severely lacking in those with RA. This study demonstrates that participants were clearly surprised that exercise could improve their sleep. Due to the multifactorial nature of RA, engaging in exercise may not only improve sleep quality but also mitigate some of its symptoms. References: [1]Kirwan JR, Boonen A, Harrison MJ, Hewlett SE, et al (2011) OMERACT 10 Patient Perspective Virtual Campus: Valuing health; measuring outcomes in rheumatoid arthritis fatigue, RA sleep, arthroplasty, and systemic sclerosis; and clinical significance of changes in health. The Journal of Rheumatology;38:1728–34. Disclosure of Interests: None declared